A Critical Analysis of China’ s Implementation of the Marrakesh Treaty - Ying Keke (SHS Web of Conferences, 2023)
Everyone has a relatively equal right to seek and access information through media and people with print disabilities should not be discriminated. To provide equal opportunity and access to information for persons with print disabilities, the Marrakesh Treaty was signed on June 27, 2013. This paper illustrates the efforts made in the newly amended Copyright Law of the People’s Republic of China and shows the challenges in the implementation of the Treaty faced by China. By comparing the practices and perspectives of different Contracting Parties, this paper focuses on the gaps and the salient issues in the current implementation in China, including the gap in the cross-border exchange, the introduction of the commercial unavailability clause, and the circumvention of technological protection measures. On this basis, potential solutions with the challenges faced by China at their core are also explored in this paper to improve the legislation and refine the supporting system in China.